2002
DOI: 10.1063/1.1492852
|View full text |Cite
|
Sign up to set email alerts
|

Inversion behavior in Sc2O3/GaN gated diodes

Abstract: The capacitance–voltage (C–V) characteristics of Sc2O3/p-GaN gate-controlled diodes show unusual hook shapes due to the charging of surface states. From the drain–voltage dependence of the C–V curves, the total surface state density was estimated to be ∼8.2×1012 cm−2 for diodes undergoing an implant activation anneal at 950 °C. The accumulation capacitance showed a significant dependence on measurement frequency and is suggested to result from the presence of an interfacial dielectric between the Sc2O3 and GaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…GaN-based MOS transistors are expected to have lower leakage currents and power consumption and capability for greater voltage swings relative to the more common Schottky-gate devices and also higher current gain cutoff frequency due to a smaller input capacitance [1][2][3][4][5][6][7][8] /eV-cm 2 (at E c -E t = 0.42 eV from AC conductance measurements) [9][10][11][12]. Gate-controlled MgO/GaN diodes exhibiting inversion characteristics have previously been reported, and these advances in realizing gated MOS diodes on GaN suggest that enhancement-mode MOSFETs are achievable [10,11]. In this paper, an initial demonstration of enhancement mode MOSFETs using MgO as a gate dielectric on p-GaN is reported.…”
Section: Introductionmentioning
confidence: 99%
“…GaN-based MOS transistors are expected to have lower leakage currents and power consumption and capability for greater voltage swings relative to the more common Schottky-gate devices and also higher current gain cutoff frequency due to a smaller input capacitance [1][2][3][4][5][6][7][8] /eV-cm 2 (at E c -E t = 0.42 eV from AC conductance measurements) [9][10][11][12]. Gate-controlled MgO/GaN diodes exhibiting inversion characteristics have previously been reported, and these advances in realizing gated MOS diodes on GaN suggest that enhancement-mode MOSFETs are achievable [10,11]. In this paper, an initial demonstration of enhancement mode MOSFETs using MgO as a gate dielectric on p-GaN is reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to make the implanted ions optically and electrically active, it is required to anneal out the implantation damage-related defects without dissociation of host atoms. Previous studies have shown that the activation of implanted impurities in III-nitride materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] is much more difficult than for conventional compound semiconductors such as GaAs and InP. A number of articles 1-8 and reviews 9-10 reporting on ion implantation studies in GaN have been published.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, there is a need for a more detailed (Received August 1, 2005; accepted December 6,2005) understanding of the electrical and optical activation properties of ion-implanted III-nitride materials, especially AlGaN.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Previous work has reported a variety of devices fabricated with the aid of ion implantation, including junction field-effect transistors, planar photodetectors, p-n junction diodes, or gated metal-oxide-semiconductor (MOS) diodes. [5][6][7][8][9][10][11][12] There is now an extensive understanding of the types of defects created in GaN and related alloys by both high and low dose implantation, the thermal stability of these defect structures, and resulting changes in the optical and mechanical properties. There is still a need for more detailed understanding of the electrical properties of implanted p/n layers in GaN because of their potential application in simple electroluminescent displays or power rectifiers.…”
Section: Introductionmentioning
confidence: 99%